Effects of acute peripheral/central visual field loss on standing balance - O’Connell, Caitlin; Mahboobin, Arash; Drexler, Scott; Redfern, Mark S.; Perera, Subashan; Nau, Amy C.; Cham, Rakié (Experimental brain research, 2017)
Vision impairments such as age-related macular degeneration (AMD) and glaucoma are among the top risk factors for geriatric falls and falls-related injuries. AMD and glaucoma lead to loss of the central and peripheral visual fields, respectively. This study utilized a custom contact lens model to occlude the peripheral or central visual fields in healthy adults, offering a novel within-subject approach to improve our understanding of the etiology of balance impairments that may lead to an increased fall risk in patients with visual field loss. Two dynamic posturography tests, including an adapted version of the Sensory Organization Test and a virtual reality environment with the visual scene moving sinusoidally, were used to evaluate standing balance. Balance stability was quantified by displacement and time-normalized path length of the center of pressure. Nine young and eleven older healthy adults wore visual field occluding contact lenses during posturography assessments to compare the effects of acute central and peripheral visual field occlusion. The results found that visual field occlusion had greater impact on older adults than young adults, specifically when proprioceptive cues are unreliable. Furthermore, the results suggest that both central and peripheral visions are important in postural control; however, peripheral vision may be more sensitive to movement in the environment.